The Individual Characteristics and Business Potential of Participant on Life Skills Education Program (PKH) in PKBM - Tasril Bartin; Wisroni Wisroni (Universitas Negeri Padang, 2019)
The purpose of this study is to describe the personal characteristics of students (learning citizens) and the business potential that is relevant to life skills education programs at the Community Learning Center in Tanah Datar District. This study uses a descriptive quantitative survey method. This study uses 60 samples from 120 population people. Furthermore, the data were analyzed quantitatively descriptive, then clarified with the focus of group discussion (FGD), interviews, observation and verification of documentation. The results showed that participants in the life skills education program in several Community Learning Centers in Tanah Datar District were generally of productive age with adequate formal education (high school level), from pre-prosperous families, and did not have a permanent business. Based on the search for interests, existing skills, and other environmental resource potentials, the appropriate business developed in the future is a business that produces goods from the agricultural sector and goods from business dress, sewing or embroidery skills.Keywords: Life Skills Education, Personal Characteristics, Business Potential